Pengaruh Model Discovery Learning Berbantuan Media Audio Visual dalam Setting Lesson Study Terhadap Hasil Belajar IPA Mahasiswa PGSD Undiksha UPP Denpasar Tahun 2017 - Lestari, Komang Putri (Universitas Pendidikan Ganesha, 2018)
This research is intended to know the influence of NHT model by audio visual media toward the mastery of science competence of fourth grade students of SD Gugus Yos Sudarso in academic year 2016/2017. Type of research conducted in this research is quantitative research with experimental design that is quasi experiment (Experimental Semu). The experimental design used is